Highly efficient visible-light-induced photocatalytic activity of Bi2WO6/BiVO4heterojunction photocatalysts - Saranyoo Chaiwichian (2018)
The Bi 2 WO 6 /BiVO 4 heterojunction photocatalysts were synthesized by hydrothermal method. Physical properties of the heterojunction photocatalyst samples were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. The XRD results indicated that BiVO 4 retain monoclinic and tetragonal structures, while Bi 2 WO 6 presented as orthorhombic structure. The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on all samples. UV-vis diffuse reflectance spectra (UV-vis DRS) were used to identify the absorption range and band gap energy of the heterojunction photocatalysts. The photocatalytic performance of Bi 2 WO 6 /BiVO 4 heterojunction photocatalysts was studied via the photodegradation of methylene blue (MB) under visible light irradiation. The results indicated that the heterojunction photocatalyst at 0.5:0.5 mole ratio of Bi 2 WO 6 :BiVO 4 shows the highest photocatalytic activity. © 2014 Elsevier Ltd. All rights reserved.